The search for environmental mechanisms underlying the expression of psychosis: introduction - Os, Jim van; Reininghaus, Ulrich; Meyer-Lindenberg, Andreas (Schizophrenia bulletin, 2017)
In this themed issue, a number of articles are presented that investigate environmental mechanisms in psychotic disorder. Below, we describe some of the challenges associated with this research, in terms of phenotypic definition, the nature of environmental impact and associated design and measurement issues.
Gesehen am 26.04.2018